PERANCANGAN SISTEM INFORMASI PKL DAN SKRIPSI YANG MAMPU MENGUKUR WAKTU PENYELESAIAN PENGAJUAN SURAT TUGAS PEMBIMBING - Donny Montreano (Bina Teknika, 2016)
Computerized information system is neededs to help the Dikjar Unit to ease business processes at Faculty of Engineering, Universitas Pembangunan Nasional "Veteran" Jakarta to input data. Therefore, it is necessary to design information systems that can support the process. As for tools and construction techniques used in this design, such as flowchart, data flow diagram (DFD) and Entity Relationship Diagram (ERD). And use of software, such as Microsoft Visual Basic 2013 as a tool for designing programs based on web, Microsoft Excel 2013 as the database that will connect with the program designed. This research was limited to only discussing about the design and internal running test. The real appliying on the Dikjar Unit will be discuss on next period of this jurnal. The end result of this research is a web-based application program that used to perform data entry preceptor of thesis and work practice, which are able to assess the performance of the Dikjar's Unit completion time.